A global review of the hinterland dimension of green port strategies. (March 2018) - Gonzalez Aregall, Marta; Bergqvist, Rickard; Monios, Jason
Highlights: First global review of green port hinterland measures. 76 out of 365 ports examined have implemented green hinterland measures. 10 measure types identified, related to different goals and challenges discussed. Most common measures are technology improvements, infrastructure and monitoring. Many otherwise world leading green ports have not implemented hinterland measures. Abstract: Despite a growing literature on strategies to reduce emissions and other externalities in shipping and ports, very little attention has been given to the port's role in reducing negative externalities in its hinterland. This paper addresses this gap by reviewing ports across the globe to identify which ports have implemented measures to improve the environmental performance of hinterland transport. Results show that only 76 out of 365 ports examined are doing so. The measures applied are identified, related to different goals and their challenges discussed. The most common measures are found to be technology improvements, infrastructure development and monitoring programmes, and the most advanced ports in green hinterland strategies are Rotterdam, Los Angeles/Long Beach and Hamburg, although many ports that are world leaders in green port strategies have not implemented measures in the hinterland dimension. Different port groups are segmented according to their mix of goals and measures as a foundation for future research.